.25x+10(.60)=x+10(.30)

Simple and best practice solution for .25x+10(.60)=x+10(.30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .25x+10(.60)=x+10(.30) equation:



.25x+10(.60)=x+10(.30)
We move all terms to the left:
.25x+10(.60)-(x+10(.30))=0
We add all the numbers together, and all the variables
.25x-(x+10(0.3))+10(0.6)=0
We add all the numbers together, and all the variables
.25x-(x+10(0.3))+6=0
We calculate terms in parentheses: -(x+10(0.3)), so:
x+10(0.3)
We add all the numbers together, and all the variables
x+3
Back to the equation:
-(x+3)
We get rid of parentheses
.25x-x-3+6=0
We add all the numbers together, and all the variables
-0.75x+3=0
We move all terms containing x to the left, all other terms to the right
-0.75x=-3
x=-3/-0.75
x=+4

See similar equations:

| 3/2x-4=x/6 | | 2n/5-4/7=8/35 | | 5x/9-7=33 | | -(6/w)=-8 | | F(x)=(2x+3)(x-2x) | | -6(-3u+6)-5u=7(u-4)-5 | | 37=-2(22-m)+3(m-3) | | -2w-25=9(w+7) | | 3x=(12)(18) | | -7(v+2)+2v+7=6v+9 | | 43x-17-3x=19+40x-36 | | 3+15y-1=9y+57-5y | | 6x^2–3=–18x | | 5x^2=3x+23 | | 0=-4z+40 | | 4x+5/8x+5x=10 | | 2b^2=100 | | 2y2−2y−5=0 | | 4(3^-2x-4)=36 | | 5x2+9x=13x−3 | | 3y2=54 | | 16=-8v+4(v+6) | | -7=7y+7(y-3) | | 33=-6x+3(x+5) | | 15x^2+7x-20=-20 | | x2−14x+17=0 | | 2x2+4=10 | | |3x+4|=|x-13| | | -2a+40+9a=3a-6a | | 2x2=10 | | 8-2x-6-13x=5 | | 12x-97=119 |

Equations solver categories